VD_FINDINFO AI 106/15 - 85/2016 vom 24. März 2016 - VD Tribunal cantonal (2016)
INFIRMITÉ CONGÉNITALE, MESURE MÉDICALE DE RÉADAPTATION, MOYEN AUXILIAIRE | 12 LAI, 13 LAI, 1 OIC, 2 al. 1 OMAI, 2 al. 2 OMAI